Analysis of Metaphorical Representation in Wordsworth’s Major Poems - Humagain, Sumargi; Humagain, Abhimanyu; Regmi, Suresh; Phuyal, Ramchandra (International Research Journal of MMC, 2023)
This study focuses on similes and metaphors that turn a simple language into a special one, known as a figurative language. This article deals with similes and metaphors executed in the major poems by William Wordsworth, one of the most influential English Romantic poets. This type of figurative language is often used in his poems with an aim to express meaning with an emphasis on the impression the poet wants to convey. The purpose of this study is to identify similes and metaphors used in his major poems. The research is based on the qualitative research to explore similes and metaphors employed in his poems and the meaning contained in each of his poems. The study mainly gets information by focusing on his four poems and pinpoints the certain words or phrases, which indicate the metaphors and similes in the poems. This research makes an effort to identify the similes and metaphors in the poems, interpret their different comparative and suggestive meanings as intended by the poet and finally turn out to be their implications. This study obviously eases the learners to gather the ideas of the figurative languages and provide them with the information to interpret the complex use of similes and metaphors. The learners will be able to define and identify metaphor and simile as the two prominent the poetic devices and write about their contribution to creating meanings in the poems.